Wnt/- Catenin Signaling Pathway Function in Uterine Leiomyoma: Potential for Therapeutic Intervention. - Ibrahim, Maria. (2017)
Abstract: Uterine leiomyoma, frequently known as fibroid, is a benign smooth muscle tumor that occurs in women between the ages of 30-55 years old. Uterine leiomyoma is a collection of hyperplastic uterine smooth muscle, along with endothelial cells, fibroblast, collagen, and sulfate proteoglycan. The prevalence f uterine leiomyoma is clinically apparent in up to 25% of women, with nearly 80 % of black women suffering from this condition. Symptoms include heavy menstrual bleeding, along with pelvic pain. Uterine leiomyoma is also the greatest contributor to infertility in the US. Currently, the mainstream method of treatment is hysterectomy, which can limit pain and bleeding symptoms, but conversely results in infertility. Major factors that may contribute to the proliferation of the leiomyoma are the decrease in the protein CCN5 and the expression of the gene HBP1--both of which are components of the Wnt signaling pathway, a fundamental pathway in normal development and in disease. CCN5 is a matricelluar protein, which has a role in cell proliferation, angiogenesis, and progression of certain cancers. CCN5 is equivalent to WISP2 (Wnt-Inducible Secreted Protein 2). There is a marked decrease of CCN5 in uterine leiomyoma as compared to the normal myometrium from the same patient. HBP1, an HMG Box transcription factor, is a cell cycle inhibitor and a transcriptional repressor of the Wnt signaling pathway. The chromosomal locus for HBP1 (7q22.3) is deleted in many fibroid tumors and HBP1 is thus a potential fibroid suppressor gene. Our preliminary results using qRT-PCR in an analysis of patient matched uterine leiomyoma and myometrium show a decrease in both the HBP1 and CCN5 mRNAs. Further analyses seek to define the Wnt signaling mechanisms and are focused on our lab's unique organotypic model of leiomyoma, in which human fibroid tumors are grown in immune-compromised mice. We plan to pharmacologically target Wnt signaling and /or CCN5 and HBP1 to potentially suppress fibroid growth. Such studies are important preludes to discovering new pharmacological interventions in a disease whose only complete "cure" is full hysterectomy.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Pharmacology & Experimental Therapeutics.; Advisors: Amy Yee, and John Castellot.; Keyword: Pharmacology.